Effect of Method of Making of Corn Flour and the Ratio of Corn Flour and Rice Flour on the Quality of Cookies - Hirda Mega Midlanda; Linda Masniary Lubis; Zulkifli Lubis (Universitas Sumatera Utara, 2014)
Corn is second search of food after rice which is found higher protein content and avalaible with affordable price. The aim of this research was to find the effect of the method of making of corn flour and ratio of corn flour and rice flour on the quality of cookies. The reseach was using completely randomized design with two factors, i.e method of making of corn flour (M) : (water addition method, modified method, and immersion in a lime solution method) and the ratio of corn flour and rice flour (T) : (90%:10%, 70%:30%, 50%:50%, and 30%:70%). Parameters analyzed were moisture content, ash content, protein content, fat content, crude fiber content, organoleptic value colour, flavor, taste, and texture. The results showed that the method of making corn of flour had highly significant effect on moisture content, ash content, protein content, crude fiber content, organoleptic value colour, taste, and texture. Ratio of corn flour and rice flour had highly significant effect on moisture content, ash content, fat content, protein content, crude fiber content, organoleptic value flavor, taste, and texture. Interaction of the two factors had highly significant effect on moisture content and protein content. Method of making of corn flour with water addition and ratio of corn and rice flour of 50%:50% produced the best cookies. Keywords : Cookies, corn, flour, rice